G237(P) Combined liver and kidney transplant for primary hyperoxaluria – another way to do it. (May 2019) - Preka, E; Samyn, M; Mamode, N; Marks, SD; Stojanovic, J
Abstract : Aim: Primary hyperoxaluria type 1(PH1) is a rare genetic paediatric disease with high morbidity and mortality and no universal evidence-based guidelines. Evidence in combined liver-kidney transplantation (CLKT) for PH1 in children is limited and variable. We report a case of a child with a complicated PH1 who to date, had unreported post-operative management with an excellent outcome. We demonstrate a different approach, which is effective and safe. Methods: A 10 year-old male with end-stage kidney disease (ESKD) secondary to PH1 diagnosed at age 5 years after presenting with chronic kidney disease and anaemia underwent CLKT. He had severe systemic oxalosis with bone marrow failure with transfusion-dependent anaemia and hypertension uncontrolled on three anti-hypertensive medications and thrice weekly haemodiafiltration. Results: Patient's pre-dialysis plasma and urine oxalate levels were ranging between 115–179 and 1200–1600 μmol/l respectively. Haemoglobin (Hb) levels were maintained above 70–75 g/L, with three weekly red blood cell transfusions. Subsequently, he developed haemosiderosis requiring oral iron chelation therapy. Blood pressure measurements were above the 95thcentile despite three anti-hypertensives and three-weekly haemodiafiltration. We decided not to perform bilateral nephrectomies before or during the transplantation. After 26 months on waiting list, he received a CLKT(38 years old deceased donor, HLA mismatch 110) without peri-operative complications. Continuous veno-venous haemodiafiltration (CVVH) was commenced at the time of liver implantation and continued for only 48 hour with primary renal allograft function. He maintained urine output >1 ml/kg/hr with a fluid target of 3–3.2 litres/day since day 1 post transplant. Potassium citrate as urinary alkalinization was continued. He had no episodes of acute rejection or nephrocalcinosis with estimated glomerular filtration rate of 60mls/min/1.73m 2 at six-month follow-up post-transplantation on prednisolone and azathioprine due to multiple infections. He is normotensive and off antihypertensive agents and has not required any blood transfusions since week 3 post transplant. Conclusion: This is the first case of a successful outcome in a CKLT in a complicated PH1 case, with CVVH requirement of only 48 hours and without native nephrectomies, with excellent liver and renal allograft function and no evidence of nephrocalcinosis at six month follow up.